HSP32 and HSP90 Immunoexpression, in Relation to Kit Pattern, Grading, and Mitotic Count in Canine Cutaneous Mast Cell Tumors. (March 2017) - Romanucci, M.; Massimini, M.; Ciccarelli, A.; Malatesta, D.; Bongiovanni, L.; Gasbarre, A.; Della Salda, L.
Literature data indicate heat shock protein (Hsp) 32 and 90 as potential molecular targets in canine neoplastic mast cells (MCs). However, their immunoexpression patterns in canine mast cell tumors (MCTs) have not been investigated. Thus, the aim of this study was to evaluate the immunohistochemical expression of Hsp32 and Hsp90 in 22 canine cutaneous MCTs, in relation to KIT immunolabeling pattern, histological grade, and mitotic count. All cases showed cytoplasmic labeling of Hsp90, variably associated with nuclear and/or membranous labeling. Relationships of Hsp90 or Hsp32 immunolabeling with KIT pattern, mitotic count, and tumor grade were not observed. However, the reduced Hsp32 immunoexpression observed in most grade III/high-grade MCTs suggests a tendency toward a loss of immunosignal in poorly differentiated MCs. The great heterogeneity in extent and distribution of Hsp90 immunoexpression among the different MCT cases may also partially explain the difficulties in predicting the in vivo biologic activity of Hsp90 inhibitors on canine MCTs.